UVA-induced weathering of microplastics in seawater: surface property transformations and kinetics - Gao, Liu; Su, Yuanyuan; Mehmood, Tariq; Wang, Zezheng; Peng, Licheng; Zhang, Naiming (Frontiers in Marine Science, 2025)
During environmental migration, large plastic fragments can undergo degradation into microplastics (MPs), posing a significant threat to ecosystems. A research gap exists in understanding how MPs age in complex environments. We modeled aging by integrating an aging index with degradation kinetics. This study investigated the degradation of MPs (polyethylene (PE), polypropylene (PP), polystyrene (PS) and polyvinyl chloride (PVC)) exposed to ultraviolet radiation in seawater. Aged MPs exhibited cracks, oxidized particles, and wrinkles on their surfaces. The functional groups experienced stretching (e.g., -OH, C-H, C=O) and bending (e.g., X-H in-plane, C-H in-plane), as identified through Fourier transform infrared spectroscopy (FTIR). Meanwhile, the crystallinity of MPs increased initially but decreased over time. The roughness and carbonyl index (CI) of MPs was increased as the weathering time progressed. mPE and mPP exhibited the most pronounced aging. The Elovich kinetic model poorly fitted the CI for aged MPs. A First-order kinetic improvement model fitted well but lacked clear parameter significance. The degradation mechanisms of mPE and mPP were similar. The benzene ring structure in mPS and dechlorination experienced by mPVC render them resistant to degradation. This study provides evidence that that enhances our understanding of the mechanisms underlying the aging process of MPs in seawater.